The hafnium and neodymium isotope composition of seawater in the Atlantic sector of the Southern Ocean - Stichel, Torben; Frank, Martin; Rickli, Jörg; Haley, Brian A. (Earth and Planetary Science Letters, 2012)
We present the first combined dissolved hafnium (Hf) and neodymium (Nd) concentrations and isotope compositions of deep water masses from the Atlantic sector of the Southern Ocean. Eight full depth profiles were analyzed for Hf and twelve for Nd. Hafnium concentrations are generally depleted in the upper few hundred meters ranging between 0.2 pmol/kg and 0.4 pmol/kg and increase to relatively constant values of around 0.6 pmol/kg in the deeper water column. At the stations north of the Polar Front (PF), Nd concentrations increase linearly from about 10 pmol/kg at depths of ~ 200 m to up to 31 pmol/kg close to the bottom indicating particle scavenging and release. Within the Weddell Gyre (WG), however, Nd concentrations are essentially constant at 25 pmol/kg at depths greater than ~ 1000 m. The distributions of both elements show a positive correlation with dissolved silicon implying a close linkage to diatom biogeochemistry. Hafnium essentially shows invariant isotope compositions with values averaging at εHf = + 4.6, whereas Nd isotopes mark distinct differences between water masses, such as modified North Atlantic Deep Water (NADW, εNd = − 11 to − 10) and Antarctic Bottom Water (AABW, εNd = − 8.6 to − 9.6), but also waters locally advected via the Agulhas Current can be identified by their unradiogenic Nd isotope compositions. Mixing calculations suggest that a small fraction of Nd is removed by particle scavenging during mixing of water masses north of the PF. Nevertheless, the Nd isotope composition has apparently not been significantly affected by uptake and release of Nd from particles, as indicated by mixing calculations. A mixing envelope of an approximated North Pacific and a North Atlantic end-member shows that Nd isotope and concentration patterns in the Lower Circumpolar Deep Water (LCDW) can be fully explained by ~ 30:70 percentage contributions of these respective end-members.